A More Perfect Union? Christian Nationalism and Support for Same-sex Unions. (September 2015) - Whitehead, Andrew L.; Perry, Samuel L.
How do overlapping social identities shape Americans' views toward contemporary social and moral issues? Drawing upon national-level data and employing the theoretical construct of social identity complexity, we examine the link between Christian nationalism–representing a convergence of national and religious identities–and Americans' views toward same-sex marriage and civil unions. Multivariate analyses reveal that greater adherence to Christian nationalism is strongly and negatively related to support for both same-sex marriage and civil unions, even after controlling for political ideology, religious controls, attribution of homosexuality, and other relevant correlates. We argue that Christian nationalists, who by definition internalize a high degree of overlap between political and religious identities, are more likely to see gays and lesbians as out-groups and same-sex unions as a threat to their sense of self and community. We conclude by discussing the implications of this study for future research on political and religious identities and intolerance toward socially marginalized populations.